UPAYA MENINGKATKAN MINAT BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA MUATAN PELAJARAN IPA - Fani Rosa Anggraini H, Saprida Napitupulu, Putri Syahpitri, Dwi Febriyanti, Nuraminah, Atika Ilma Si (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The research aims to increase students' interest in learning through the team games tournament (TGT) learning model in class V science lesson content at SD Negeri 101952 Tualang. The method used in this research is the classroom action research method through 2 cycles, where each cycle has stages, namely: Planning, Implementation, Evaluation and Reflection. The subjects in this research were teachers and 22 class V students at SDN101952 Perbaungan. The data collection techniques used were observation techniques and questionnaires. Data analysis techniques use data reduction, explaining data, verifying activities, analyzing observation results, and drawing conclusions. The results of the research show: the learning interest of students who are taught using the teams game tournament (TGT) type cooperative learning model can increase, there is an increase in the learning interest of class V students, where in the initial test using a questionnaire the average result obtained was 61.54 in cycle I it increased to 71.54 then in cycle II there was an increase again to 86.92. Activities for students' interest in learning also improved in cycle II when compared to cycle I. Where in cycle I writing and reading activities fell from 50.80 to 20.30, activities working on LKS from 30.05 to 46.30, asking friends from 12.50 to 19.63%, asking teachers from 12.30 to 8.80, irrelevant activities from 17.70 to 5.50. This proves that students' interest in learning is getting better in cycle II when compared to cycle I.